PENGARUH KONDISI EKONOMI KELUARGA, MOTIVASI BELAJAR, DAN GAYA BELAJAR TERHADAP HASIL BELAJAR SISWA - Rejeki, Sri (Jurnal Informasi dan Komunikasi Administrasi Perkantoran, 2012)
Abstract: The purpose of this study was to (1) determine the direct influence of economic conditions of the learning outcomes of students in SMK Murni 2 Surakarta in academic year 2011/2012, (2) determine the direct influence of motivation on learning outcomes of students in SMK Murni 2 Surakarta in academic year 2011 / 2012, (3) determine the direct influence of learning style on learning outcomes of students in SMK Murni 2 Surakarta academic year 2011/2012, (4) determine the effect of indirect economic conditions of the learning outcomes of students with learning styles in SMK Murni 2 Surakarta in academic year 2011 / 2012, (5) determine the effect of indirect motivation on learning outcomes of students with learning styles in SMK Murni 2 Surakarta in academic year 2011/2012. The results of this study were (1) there is a direct influence on the economic conditions of student learning outcomes, (2) there is a direct effect of motivation on learning outcomes, (3) there is a direct influence of learning style on learning outcomes, (4) there is an indirect effect of condition family income on student learning outcomes through learning styles, and (5) there is an indirect effect of motivation on learning outcomes through learning styles. Keywords: family economic conditions, motivation, learning styles,